062 Re-appraisal of ECG interpretation in young athletes: should axis deviation and voltage criterion for atrial enlargement be categorised as abnormal in athletes? The British experience. (16th May 2012) - Gati, S; Ghani, S; Zaidi, A; Sheikh, N; Papadakis, M; Von Nierkerk, N; Chen, L; Reed, M; Sharma, S
Abstract : Purpose: The European Society of Cardiology (ESC) guidelines for ECG interpretation in athletes facilitate the differentiation of physiological changes (Group 1) representing cardiac adaptation from those potentially associated with an increased cardiovascular risk (Group 2). Increased false positive rates remain the downside of electrocardiographic evaluation in athletes. The aim of this study was to assess whether axis deviation and atrial enlargement in isolation require further investigation in highly trained athletes. Methods: Between 2003 and 2011, 1843 highly trained athletes (66% males) (mean age 20.7±6.0 years); range 14–35 years, underwent cardiac evaluation with 12-lead ECG and echocardiography. ECGs were analysed for training-unrelated changes, according to the ESC guidelines. Results: Of the 1843 athletes, 1309 athletes (71%) demonstrated training related (Group 1) changes and 184 athletes (10%) exhibited training-unrelated (Group 2) changes. Of the Group 2 ECG changes, atrial enlargement and axis deviation in isolation were identified in 7.2% of athletes. Athletes with atrial enlargement or axis deviation did not exhibit significant difference in left ventricular end-diastolic cavity size >54 mm (35.6% vs 27.9% p=0.1005), mean right atrial dimension (41.4 mm±5.6 mm vs 42.0 mm ±26.4 mm; p=0.848) or fractional shortening (2.5% vs 3.8%; p=0.7881) compared with athletes with Group 1 changes. The mean left atrial dimension in athletes with atrial enlargement/axis deviation was greater than in athletes with Group 1 changes (35.6 mm ±5.58 mm vs 33.4 mm ±5.26 mm; p=<0.0001). Athletes with atrial enlargement and axis deviation revealed a higher prevalence of left ventricular hypertrophy (LVWT >12 mm) (8.5% vs 3.1%; p=0.0209), right ventricular enlargement (RVID1 >42 mm) (38.9% vs 29.4%; p=0.0412) compared with athletes with Group 1 changes. None of the athletes with axis deviation/atrial enlargement exhibited valve disease, or any features of hypertrophic cardiomyopathy or arrhythmogenic right ventricular cardiomyopathy. Conclusion: Atrial enlargement and axis deviation are relatively common in highly trained athletes. Subsequent investigation with echocardiography reveals slightly greater dimensions but has a low diagnostic yield for cardiac disease. Exclusion of these ECG parameters from the Group 2 category in asymptomatic athletes would reduce the false positive rate from 10% to an acceptable <3%.